2017
DOI: 10.3390/toxins9060193
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hemagglutinin Negative Botulinum Progenitor Toxins

Abstract: Botulism is a disease involving intoxication with botulinum neurotoxins (BoNTs), toxic proteins produced by Clostridium botulinum and other clostridia. The 150 kDa neurotoxin is produced in conjunction with other proteins to form the botulinum progenitor toxin complex (PTC), alternating in size from 300 kDa to 500 kDa. These progenitor complexes can be classified into hemagglutinin positive or hemagglutinin negative, depending on the ability of some of the neurotoxin-associated proteins (NAPs) to cause hemaggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…In several studies, no stable complex of BoNT/ A2 with any OrfX-protein has been found. Only the M-PTC consisting of BoNT and NTNH has been identified [2,26,52]. This was also the case in this study using recombinant proteins (Fig.…”
Section: Orfx Cluster General Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In several studies, no stable complex of BoNT/ A2 with any OrfX-protein has been found. Only the M-PTC consisting of BoNT and NTNH has been identified [2,26,52]. This was also the case in this study using recombinant proteins (Fig.…”
Section: Orfx Cluster General Discussionsupporting
confidence: 74%
“…OrfX2, OrfX3, and P47 have been shown to be expressed in cell cultures of Clostridium botulinum A2 Kyoto [2]. For the HA cluster of BoNT/A1, it has been shown that the growth media and culture condition play a role in what type of complex is formed from the NAPs [15,53,54], and a similar situation could be the case for the OrfX cluster of BoNT/A2 [26].…”
Section: Orfx Cluster General Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Finally, the toxin gene is expressed along with several other toxin cluster genes as part of a botulinum toxin complex. The toxin-associated genes are known as either the hemagglutinin ( ha+ ) cluster or orfX ( orfX+ ) cluster, and are associated with different toxin types: BoNT/A, /B, /C, /D and /G are associated with HA complex proteins, while BoNT/A, /E and /F are associated with one or more orfX proteins [ 13 ].…”
Section: Introductionmentioning
confidence: 99%